2005
DOI: 10.1007/s00296-005-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous lumbar traction on the size of herniated disc material in lumbar disc herniation

Abstract: We investigated the effects of continuous lumbar traction in patients with lumbar disc herniation on clinical findings, and size of the herniated disc measured by computed tomography (CT). In this prospective, randomized, controlled study, 46 patients with lumbar disc herniation were included, and randomized into two groups as the traction group (24 patients), and the control group (22 patients). The traction group was given a physical therapy program and continuous lumbar traction. The control group was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 14 publications
0
44
0
3
Order By: Relevance
“…176,[242][243][244][245][246][247][248][249][250] One further study compared mixed treatment that included traction, with mixed treatments or with other comparators without traction (Table 57a). [253][254][255][256] Three studies compared different types of traction (Table 57b). 248,251,252 Summary of study participants for traction Summary data for included participants are presented in Table 58.…”
Section: Tractionmentioning
confidence: 99%
“…176,[242][243][244][245][246][247][248][249][250] One further study compared mixed treatment that included traction, with mixed treatments or with other comparators without traction (Table 57a). [253][254][255][256] Three studies compared different types of traction (Table 57b). 248,251,252 Summary of study participants for traction Summary data for included participants are presented in Table 58.…”
Section: Tractionmentioning
confidence: 99%
“…isokinetic muscle test [4]). Nineteen measures were described in a vague or uninformative manner that would preclude replication [6,11,26,31,33,43,49,59,70,74,81,87,93,95,100]. Seventeen studies used a minimum level of pain or 'symptoms' as a proxy for recovery; however, no two studies did so in exactly the same way (Table 1).…”
Section: Data Extractionmentioning
confidence: 99%
“…Administrative data were used in four studies; two used return to work as the criterion [34,35,91], and two used time to insurance claim closure [14,34,35], and one further study used a self-rating of return to work [44] ( Table 4). Six studies measured physical performance or absence of neurological deficits [4,11,29,47,74,95], however in only three of these studies [4,29,47] was the test clearly described. Another aspect of recovery that varied widely among included studies is the duration for which patients had to meet the recovery criteria to be regarded as recovered.…”
Section: Searchmentioning
confidence: 99%
“…Spinal traction is generally regarded as a conservative management in treating various types of neck or back disorders. Several mechanisms have been proposed for the possible therapeutic effects of traction [5,10,17,21,27,28,36]. DeLacerda et al [5] reported that the axial traction reduced pain by improving circulation or preventing adhesions and contractures of spinal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Krause et al [17] concluded that the separation of vertebrae by increasing the diameter of intervertebral foramen could reduce radicular pain and normalize neurological deficits by relieving direct pressure or contact forces in the sensitized neural tissues. Although the exact mechanisms for pain relief and function recovery are still controversial, the generally recognized biomechanical effects of cervical traction are to enlarge the intervertebral disc spaces around foramen levels and tighten the posterior longitudinal ligament [17,21,27,28,36].…”
Section: Introductionmentioning
confidence: 99%